Neuronal influence behind the central nervous system regulation of the immune cells - CHAVARRIA, ANAHI; Cárdenas, Graciela (Frontiers in Integrative Neuroscience, 2013)
Central nervous system (CNS) has a highly specialized microenvironment, and despite being initially considered an immune privileged site, this immune status is far from absolute because it varies with age and brain topography. The brain monitors immune responses by several means that act in parallel; one pathway involves afferent nerves (vagal nerve) and the other resident cells (neurons and glia). These cell populations exert a strong role in the regulation of the immune system, favoring an immune-modulatory environment in the CNS. Neurons control glial cell and infiltrated T-cells by contact-dependent and -independent mechanisms. Contact-dependent mechanisms are provided by several membrane immune modulating molecules such as Sema-7A, CD95L, CD22, CD200, CD47, NCAM, ICAM-5, and cadherins; which can inhibit the expression of microglial inflammatory cytokines, induce apoptosis or inactivate infiltrated T-cells. On the other hand, soluble neuronal factors like Sema-3A, cytokines, neurotrophins, neuropeptides, and neurotransmitters attenuate microglial and/or T-cell activation. In this review, we focused on all known mechanism driven only by neurons in order to control the local immune cells.